Tobacco Smoking in People Is Not Associated with Altered 18-kDa Translocator Protein Levels: A PET Study - Hillmer, Ansel T. (J Nucl Med, 2020)
The effects of tobacco smoking on the immune system of the brain are not well elucidated. Although nicotine is immunosuppressive, other constituents in tobacco smoke have inflammatory effects. PET imaging of the 18-kDa translocator protein (TSPO) provides a biomarker for microglia, the primary immunocompetent cells of the brain. This work compared brain TSPO levels in 20 tobacco smokers (abstinent for at least 2 h) and 20 nonsmokers using a fully quantitative modeling approach for the first time, to our knowledge. Methods: (11)C-PBR28 (N-((2-(methoxy-(11)C)-phenyl)methyl)-N-(6-phenoxy-3-pyridinyl)acetamide) PET scans were acquired with arterial blood sampling to estimate the metabolite-corrected input function. (11)C-PBR28 volumes of distribution were estimated throughout the brain with multilinear analysis. Results: Statistical analyses revealed no evidence of significant differences in regional (11)C-PBR28 volumes of distribution between smokers and nonsmokers (whole-brain Cohen d = 0.09) despite adequate power to detect medium effect sizes. Conclusion: These findings inform previous PET studies reporting lower TSPO radiotracer concentrations in the brain (measured as SUV) for tobacco smokers than for nonsmokers by demonstrating the importance of accounting for radiotracer concentrations in plasma. These findings suggest that nonsmokers and smokers have comparable TSPO levels in the brain. Additional work with other biomarkers is needed to fully characterize the effects of tobacco smoking on the brain immune system.